Implementation of Participative Management to Improve Employee Performance from a Philosophical Perspective - kusuma, Ginanjar Indra; Suprianto (Contemporary Journal of Applied Sciences, 2024)
This study examines the implementation of participative management from a philosophical perspective to improve employee performance. This study combines analytical descriptive research methods with a qualitative approach . The results of the study indicate that participative management increases employee involvement in decision making, creates a more family-like work atmosphere, and improves communication between leaders and employees. Although no direct relationship was found between participative management and improved performance, increased job satisfaction resulting from participation has been shown to encourage employees to be more productive and support organizational goals. Therefore, organizations are advised to implement participative management by creating an inclusive work environment and open communication to achieve long-term goals